Self-compassion Guru yang berperan sebagai Shadow - Mistiani Mistiani; Suryani Suryani (Fakultas Psikologi Universitas Negeri Malang, 2021)
This study was conducted to explore the self-compassion of shadow teacher. The analysis used in this study was a phenomenological model with triangulation as a technique to validate the data. This study involved three shadow teachers as participants. The results showed that the three participants had self-compassion which could be shown or expressed in different ways.